Reliability And Accuracy of Bite Mark Analysis In Forensic Odontology - Thete, Sanjay Gangadhar; umbare, DhirajKumar Kashinath; Namazi, Nasim; Kothawade, Sakshi; Bajaj, Sejal; Thete, Sankarshan Sanjay (Journal of Neonatal Surgery, 2025)
Background: Bite mark analysis is a forensic technique used to link suspects to criminal investigations based on unique dental patterns. The accuracy of bite mark evidence has been debated due to variations in human dentition, the quality of bite marks, and subjectivity in analysis. This study evaluates the reliability of bite mark analysis by comparing traditional and advanced methodologies. Objective: To assess factors influencing the accuracy of bite mark analysis. To compare the effectiveness of traditional forensic odontology techniques with advanced 3D imaging and computer-assisted analysis. To provide recommendations for improving the reliability of bite mark analysis in forensic investigations. Methods: A cross-sectional study was conducted with 50 participants, equally distributed by gender. Bite marks were obtained using standardized wax wafers, and dental impressions were created using dental stone. Traditional visual analysis was compared with 3D imaging and computerassisted analysis. Statistical analysis was performed using SPSS v21.0, with accuracy rates, sensitivity, specificity, and p-values evaluated. Results: Traditional bite mark analysis showed an accuracy rate of 75%, while 3D imaging achieved 90% and computer-assisted analysis 92%. Bite marks remained identifiable up to 48 hours, after which degradation affected reliability. Factors such as bite mark clarity, elapsed time, and anatomical variations significantly influenced accuracy. Gender-based differences in bite mark patterns were observed, with statistically significant variations (p < 0.05). Conclusion: Bite mark analysis remains a valuable forensic tool but requires technological integration to improve reliability. 3D imaging and computer-assisted analysis significantly enhance accuracy over traditional methods. Standardized protocols and further research on environmental factors affecting bite mark degradation are essential for forensic applications.